Polysaccharide fucoidan BAM1 antibody binding in porewater samples from coastal vegetated ecosystems - Inga Hellige; Dariya Baiko; Jana K Geuer; Bruna Imai (PANGAEA, 2025)
Porewater of saltmarsh, seagrass and unvegetated areas around the German Bight in 2022 and 2023 was sampled at 50cm depth. A transect of up to 9 points per ecosystem were sampled. Polysaccharides >5kDa were upconcentrated using AMICON-filtration device, freeze dried and dried samples were resuspended in MilliQ-water. Polysaccharides were screened for fucoidan BAM1 antibody binding using ELISA method, according to Cornuault et al. (2014).